Chronology and Typology of Wallpaper in the World until the 19th Century A. D. and the Encounter of Qajar Courtiers with it - Zahra Babaei Kalemasihi; Melika Yazdani (پیکره)
Introduction: Wallpaper is one of the oldest and the most widely used decorations in interior architecture in the world, and it has undergone numerous changes so far. Also, besides the evolution in the methods of producing, implementing, and renovating, as well as the complexity and ambiguity of the developments related to this decoration, the sources of its evolution and production methods have been limited and scattered. At the same time, how wallpaper entered Iran, the pioneers of wallpaper in Iran, and their style of choosing types of wallpaper have been largely neglected. The questions of the present research are: «Who are the pioneers of wallpaper in the world and Iran?», «How was the Qajar courtiers' encounter with wallpaper technology?», and «In the evolution of wallpaper, what factors directed this industry to reach its present form?»Research Method: The present research is conducted using a descriptive-analytical method, and its data collection is based on the field, library, and internet sources.Findings: The results indicate that despite the distinct opinions of researchers, in the middle of the 15th century, the French pioneered the use of wallpaper in today's sense. The variety in design, color, implementation, and installation could transform it from a worthless product to a product that is a sign of aristocracy and luxury. Therefore, it was used in the homes of kings, courtiers, and merchants in Europe and Iran during the Qajar period. Naser al-Din Shah was the first addressee of this product in Iran. After him, the Qajar courtiers used imported wallpapers to satisfy the sense of modernity and keep pace with the global style. Another finding of the present study is the extent of the design, motif, technique, and space used for wallpaper in Vasigh Ansari's House, which has turned this collection into a wallpaper treasure of the Qajar period.Conclusion: China (due to the invention of paper and its various uses) and France (due to inventions and progress in wallpaper production until the 19th century) can be considered the founders of wallpaper. Concerning the coincidence of the Era of Naser al-Din Shah with the popularity of wallpaper in the Victorian period, it can be said that the use of wallpaper in Iran by the Qajar court is a reflection of global taste and the political-social conditions of this era.